ChemInform Abstract: Synthesis of Polycyclic Aminocyclobutane Systems by the Rearrangement of N‐(ortho‐Vinylphenyl) 2‐Azabicyclo[3.1.0]hexane Derivatives. Issue 3 (21st January 2014) - Wasilewska, Agnieszka; Wozniak, Bartosz A.; Doridot, Gabriel; Piotrowska, Kamila; Witkowska, Natalia; Retailleau, Pascal; Six, Yvan
Abstract The synthesis of the title compounds strongly depends on the applied conditions and the substitution pattern.